2017
DOI: 10.3892/ol.2017.6306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Snail and E-cadherin expression in pancreatic neuroendocrine tumors

Abstract: Abstract. Pancreatic neuroendocrine tumors (PNETs) are a rare type of malignancy with a prognosis that is relatively good, compared with that of pancreatic adenocarcinoma. However, a number of patients with PNETs have distant metastasis and a less favorable prognosis. Epithelial-mesenchymal transition (EMT) is essential for tumor progression and metastasis. Snail and E-cadherin serve key roles in the process of EMT in numerous tumor types, including gastric and pancreatic adenocarcinoma. However, the role of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The findings were consistent with NMT phenotype. Of note, the E-cadherin signal in BON cells had an atypical nuclear distribution, similar to that previously shown to correlate with invasiveness in pancreatic NETs [ 34 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The findings were consistent with NMT phenotype. Of note, the E-cadherin signal in BON cells had an atypical nuclear distribution, similar to that previously shown to correlate with invasiveness in pancreatic NETs [ 34 ].…”
Section: Resultssupporting
confidence: 81%
“…In BON cells that express both epithelial and neuroendocrine features, this can be achieved via neuroendocrine-to-mesenchymal transition (NMT). This transition is characterized by a reduction in neuroendocrine markers and altered expression of mesenchymal proteins [ 32 34 ]. Thus, we assessed whether AA treatment could induce morphological changes and alter expression of markers of NMT including chromogranin A (CGA) E-cadherin, α-smooth muscle actin (α-SMA) and snail family transcriptional repressor 1 (Snail1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to other cancers, NET cells may acquire invasive potential through the epithelial-to-mesenchymal transition (EMT), a transdifferentiation program conferring mesenchymal plasticity to epithelial cells [20]. Multiple studies have demonstrated that the EMT drives the progression of both well- and poorly differentiated NETs, and that EMT-undergone tumors have a dismal prognosis, as demonstrated by the association between poor outcomes and the overexpression of EMT-related factors including snail, slug, twist and vimentin in tumor cells [21-27]. In this context, bone-colonizing NETs have been shown to harbor specific EMT-related features.…”
Section: Bone Metastases In Nets: Molecular Pathogenesismentioning
confidence: 99%
“…To date, a few studies have been conducted to evaluate the expression of EMT-specific transcription factors in neuroendocrine tumors [ 26 28 ]. Fendrich et al immunohistochemically evaluated the expression of the EMT factors Snail, Twist and E-cadherin in human pNETs and showed overexpression of Snail and Twist and loss of E-cadherin expression in the majority of malignant pNETs [ 26 ], which was similar to the results of Yonemori K [ 29 ]. However, no statistically significant correlation was found between Snail/Twist expression or loss of E-cadherin expression and OS, but there was an inverse association between E-cadherin and Snail/Twist.…”
Section: Discussionmentioning
confidence: 55%